Principles of Diabetes Mellitus - Poretsky, Leonid (Springer US : Imprint: Springer, 2010)
Principles of Diabetes Mellitus, Second Edition is an important update to the comprehensive textbook first published in 2002 and reissued in 2004. It is written for physicians of all specialties who, on a daily basis, deal with an illness which has reached epidemic proportions. The book is also intended for medical students and investigators of all aspects of diabetes. The last five years have witnessed major developments in our understanding of diabetes and in therapeutic approaches to this disease. Thus, in addition to updating all chapters, the authors added eight new chapters to the second edition. Principles of Diabetes Mellitus, Second Edition covers diabetes in all of its aspects-genetics, epidemiology, pathophysiology, clinical manifestations, therapy and prevention.